Obtención de compuestos orgánicos oxigenados por pirólisis de la pepa de mango. - Paredes Aranda, José Miguel (2012)
It study the production of oxygenated organic compounds by pyrolysis of mango pit is studied. the influence of the reaction temperature, nitrogen flow, humidity and particle size of the raw material is investigated. the functional groups are identified by infrared spectroscopy with Fourier transform of the liquid product obtained in the organic and aqueous phase. The results show that increasing the reaction temperature influences cyclically in the product, indicating a dynamic formation-destruction of the functional groups. Thus, when at a temperature forming functional groups in organic compounds in aqueous compositions is opposite effect is favored. The nitrogen flow in the range of 30 to 150 cm3 min-1, does not influence the formation-destruction of the functional groups present in organic and aqueous compounds, but 200 cm3 min-1 adversely affects the yield of liquid product total. Humidities in the raw material between 9.5 and 17.7% positively influences the formation of oxygen functional groups in the organic and aqueous compounds. dry or high moisture content (> 17.7%) samples do not favor the formation of functional groups. Particle sizes between 4.75 mm + 2.36- favors the formation of both functional groups in organic compounds and aqueous.